Management of microbial resources in the environment - Abdul Malik; Alves, Madalena; Grohmann, Elisabeth (Springer, 2013)
This volume details the exploration, collection, characterization, evaluation and conservation of microbes for sustainable utilization in the development of the global as well as national economies, e.g. in agriculture,ecosystems, environments, industry and medicine. Many research institutes and universities all over the world carry out microbiological and biotechnological research, which generates substantial genomic resources such as cDNA libraries, gene constructs, promoter regions, transgenes and more valuable assets for gene discovery and transgenic product development